Can the Implementation of the Water-Energy-Food Nexus Support Economic Growth in the Mediterranean Region? The Current Status and the Way Forward - Vasileios Markantonis; Arnaud Reynaud; Armagan Karabulut; Rana El Hajj; Dogan Altinbilek; Ibrahim M. Awad; Adriana Bruggeman; Vangelis Constantianos; Jaroslav Mysiak; Nicola Lamaddalena; Mohamed Salah Matoussi; Monteiro, H.; et al. (Frontiers in Environmental Science, 2019)
Water resources is a crucial environmental good for the function of the human societies and the ecosystems. Moreover, water is an important input for the economy and an indispensable factor for economic growth. Especially in regions that are facing water scarcity, the adoption of water management policies and approaches fostering the sustainable use of resources while promoting economic growth becomes an emerging issue. The Mediterranean region is one of the most vulnerable regions regarding the availability of water resources due to climate change and human activities. The Water-Energy-Food (WEF) Nexus offers an integrated approach analyzing the synergies and trade-offs between the different sectors in order to maximize the efficiency of using the resources, whereas adapting optimum policies and institutional arrangements. The Mediterranean is a region where we observe a large spectrum of issues emanating from water pollution and natural resource degradation to water scarcity, large amounts of food loss and waste and increasing demand for energy and food. Agricultural practices, urban development, demand management for water, and protection of ecosystems, particularly aquatic ecosystems, are areas of particular intervention available to the decision-makers in enhancing availability of water for the various water using sectors. In this context, the current policy note paper aims to address a major issue: how can the implementation of the WEF Nexus support the economic growth in the Mediterranean? Based on the outcome of an experts and stakeholders regional workshop, this paper presents the current status, including the opportunities and the practices of applying the WEF Nexus in the Mediterranean and draws specific recommendations for the way forward. Regarding the later, the strengthening of WEF Nexus in the Mediterranean requires a set of interventions to strengthen the institutional capacities, to enhance the finance mechanisms, to support the intra-regional dialogue as well, to enhance data collection and management, as well as to implement economic instruments and integrated economic approaches to measure the impact of Nexus into economy and employment.